2020
DOI: 10.21203/rs.3.rs-47479/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of adherence between fixed and unfixed topical combination glaucoma therapies using Japanese healthcare/pharmacy claims database: A retrospective non-interventional cohort study

Abstract: Background: Adherence to chronic therapies is crucial to prevent the progression of disease, such as glaucoma. However, only a limited number of studies have investigated them using real-world data in Japan. This study aimed to evaluate Japanese patients’ adherence to fixed- and unfixed-combination eye drops as a second-line therapy for glaucoma in real-world practice.Methods: This retrospective, non-interventional cohort study utilized a commercially available Japanese healthcare database (MinaCare database).… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 20 publications
(24 reference statements)
0
10
0
7
Order By: Relevance
“…Behandlungsjahr ein Adhärenzniveau von durchschnittlich 60 – 70% aufgrund der Anzahl an eingelösten Verschreibungen feststellen 15 , 16 . Es zeigt sich, dass in Japan Fixkombinationen mit 79,1% deutlich häufiger aus Apotheken abgeholt wurden als Nicht-Fixkombinationen (62,2%) 16 . Dichotomisiert auf ein PDC ≥ 80% zeigt sich, dass nur etwa 50% der Patienten eine gute Adhärenz aufweisen 15 , 16 , 17 .…”
Section: Adhärenz Beim Glaukomunclassified
“…Behandlungsjahr ein Adhärenzniveau von durchschnittlich 60 – 70% aufgrund der Anzahl an eingelösten Verschreibungen feststellen 15 , 16 . Es zeigt sich, dass in Japan Fixkombinationen mit 79,1% deutlich häufiger aus Apotheken abgeholt wurden als Nicht-Fixkombinationen (62,2%) 16 . Dichotomisiert auf ein PDC ≥ 80% zeigt sich, dass nur etwa 50% der Patienten eine gute Adhärenz aufweisen 15 , 16 , 17 .…”
Section: Adhärenz Beim Glaukomunclassified
“…In a cohort study in Japan, most patients prescribed a combination of a prostaglandin analogue and a beta-blocker (Shirai et al 2021). The study also showed that the fixed combination of latanoprost + timolol was high with a percentage of 54.5% (Shirai et al 2021).…”
Section: Combinations Drugs Therapymentioning
confidence: 99%
“…In a cohort study in Japan, most patients prescribed a combination of a prostaglandin analogue and a beta-blocker (Shirai et al 2021). The study also showed that the fixed combination of latanoprost + timolol was high with a percentage of 54.5% (Shirai et al 2021). The combination of prostaglandin analogues and beta-blockers is a good combination because of the high effectiveness of each drug class.…”
Section: Combinations Drugs Therapymentioning
confidence: 99%
“…7 Our database study also demonstrated that fixed-combination therapy was associated with greater adherence than unfixed therapy. 8 Specifically, latanoprost/timolol fixed-combination therapy for glaucoma has a high adherence rate. It lowers IOP more potently than unfixed-combination latanoprost or timolol monotherapy, 9 and was developed with the aim of reducing the number of eye drops (reducing patient burden), avoiding the washout effect due to an inadequate interval of instillation time (reducing the drug's efficacy), and reducing preservative exposure (reducing the risk of ocular surface disease).…”
Section: Introductionmentioning
confidence: 99%
“… 7 Our database study also demonstrated that fixed-combination therapy was associated with greater adherence than unfixed therapy. 8 …”
Section: Introductionmentioning
confidence: 99%